2021
DOI: 10.1007/s00247-021-05235-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the vocal cords in infants

Abstract: Vocal cord paralysis is a common cause of respiratory and feeding problems in the pediatric population. While the causes of vocal cord paralysis are multiple, iatrogenic injury of the recurrent laryngeal nerve after cardiovascular surgery is the most frequent cause. Vocal cord paralysis increases the risk of swallowing dysfunction, tracheal aspiration and pneumonia. It also increases the need for nasoenteric feeds and gastrostomy tube placement. Flexible nasopharyngolaryngoscopy is considered the gold standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In recent years, several studies have demonstrated the usefulness of ultrasound for evaluating vocal cords of children. 22,23 The ultrasound examination is better tolerated than FL by children, but this is dependent on the skills of the physician performing the examination. Furthermore, bilateral VCP has been reported to be difficult to evaluate by ultrasound examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have demonstrated the usefulness of ultrasound for evaluating vocal cords of children. 22,23 The ultrasound examination is better tolerated than FL by children, but this is dependent on the skills of the physician performing the examination. Furthermore, bilateral VCP has been reported to be difficult to evaluate by ultrasound examination.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of DDR, such as the absence of pain, ease of use by non‐otolaryngologists, and absence of the risk of droplet infection, are expected to increase its use in clinical settings. In recent years, several studies have demonstrated the usefulness of ultrasound for evaluating vocal cords of children 22,23 . The ultrasound examination is better tolerated than FL by children, but this is dependent on the skills of the physician performing the examination.…”
Section: Discussionmentioning
confidence: 99%